Statement on the safety of taxifolin‐rich extract from Dahurian Larch (Larix gmelinii). (13th November 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to carry out a supplementary safety assessment for taxifolin by considering also those population groups which were originally excluded at the request of the applicant (i.e. infants, young children and children up to 9 years) for the food categories set out in the application, and by taking into the extension of use of taxifolin from yogurt to a wider range of dairy products. In 2016, the EFSA NDA Panel adopted the Scientific Opinion on the safety of taxifolin‐rich extract from Dahurian Larch ( Larix gmelinii ) as a novel food ingredient in non‐alcoholic beverages, yogurts, chocolate confectionery and food supplements pursuant to Regulation (EC) No 258/97. In order to address the present mandate, an intake assessment was carried out by taking into account all population groups (including now also children below 9 years of age) and by considering the food intended categories for which the applicant provided maximum use levels of taxifolin. Intakes were estimated for all age groups of the general population. The highest 95th percentile intakes per kg bw per day among all population groups are 0.94 and 1.54 mg, respectively, derived for toddlers. Noting that the no‐observed‐adverse effect level (NOAEL) of the subchronic study was 1, 500 mg/kg body weight (bw), the resulting margin of exposure (MOE) would be almost 1, 000. For adults weighing 70 kg, the MOE to the combined intake from fortified foods and food supplements would be about 772. For adolescents, taking into account a default mean body weight of 61 kg, the MOE to the combined intake (including 100 mg from food supplements) would be about 627. The Panel considers that these MOEs are sufficient. The Panel concludes that the NF food, taxifolin‐rich extract from Dahurian Larch, is safe under the proposed conditions of use.